2006
DOI: 10.1021/es0601787
|View full text |Cite
|
Sign up to set email alerts
|

Polyaromatic Hydrocarbon and PAH Metabolite Burdens in Oiled Common Guillemots (Uria aalge) Stranded on the East Coast of England (2001−2002)

Abstract: Aside from the physical effects of oiling (e.g., hypothermia, dehydration, emaciation), chronic toxicity of polycyclic aromatic hydrocarbons (PAHs) contamination is an important factor influencing long-term recovery of oiled sea birds following an oil spill. Monitoring PAH exposure can help identify populations at risk from toxic effects of PAHs for further study and/or protection. This is the first studyto quantify PAH and metabolite tissue burdens in sea birds directly oiled following oil spills. PAHs and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 27 publications
2
40
2
Order By: Relevance
“…N PH) is not as efficient as metabolism of HMWAHs (e.g. BaP) in some species of fish and birds (Roubal et al 1977, Varanasi & Gmur 1981, Jonsson et al 2004, Troisi et al 2006. Data collected in the current study clearly demonstrated that externally oiled turtles had absorbed petroleum-related PAHs via ingestion as well as inhalation (based on gastrointestinal and lung PAH findings, respectively), and that they had metabolized these compounds in the liver to more polar fluorescent aromatic compounds that were measured in their bile.…”
Section: Tissue Differences In Pah Concentrations and Implications Fomentioning
confidence: 99%
“…N PH) is not as efficient as metabolism of HMWAHs (e.g. BaP) in some species of fish and birds (Roubal et al 1977, Varanasi & Gmur 1981, Jonsson et al 2004, Troisi et al 2006. Data collected in the current study clearly demonstrated that externally oiled turtles had absorbed petroleum-related PAHs via ingestion as well as inhalation (based on gastrointestinal and lung PAH findings, respectively), and that they had metabolized these compounds in the liver to more polar fluorescent aromatic compounds that were measured in their bile.…”
Section: Tissue Differences In Pah Concentrations and Implications Fomentioning
confidence: 99%
“…1,2 The processes of industry and domestic sewage in human lives and the use of agricultural fertilizer lead to water pollution. [4][5][6][7] They have low solubility in water but are delivered through the food chain and finally harm human health. [4][5][6][7] They have low solubility in water but are delivered through the food chain and finally harm human health.…”
Section: Introductionmentioning
confidence: 99%
“…PAHs in the fish were mostly dominated by the high molecular weight PAHs (4 -6 rings). Several studies [62] [63] have shown that fish preferentially bioaccumulate 4, 5 and 6 ringed PAHs rather than 2, 3 ringed PAHs. In …”
Section: Chemical Analysismentioning
confidence: 99%